Efficient 3D charge transport in planar triazatruxene-based dumbbell-shaped molecules forming a bridged columnar phase. Issue 43 (29th October 2021) - Jing, Jiang; Heinrich, Benoît; Prel, Alexis; Steveler, Emilie; Han, Tianyan; Bulut, Ibrahim; Méry, Stéphane; Leroy, Yann; Leclerc, Nicolas; Lévêque, Patrick; Rosenthal, Martin; Ivanov, Dimitri A.; et al.
Abstract : Triazatruxene-based dumbbell-shaped molecules self-assemble into a novel bridged columnar phase, where conducting segments connect adjacent columns of triazatruxene units across the insulating aliphatic domains, resulting in efficient hole transport in 3D. Abstract : Planar conjugated molecular backbones are essential for achieving high charge carrier mobilities along molecular π-stacking directions but are often concomitant with poor charge transport in other directions. This is particularly the case for molecules that are functionalized with alkyl chains, which ensure good processability in solution but introduce detrimental insulating regions. Here, we show that soluble planar dumbbell-shaped molecules, composed of two triazatruxene (TAT) units covalently bonded to a central thiophene–thienopyrroledione–thiophene (TPD) segment self-assemble into an original structure that allows efficient 3D charge transport. Grazing-incidence wide-angle X-ray scattering investigations as well as micro-focus X-ray experiments on single crystals reveal that the TAT derivatives form a columnar-nematic mesophase in which columns of stacked TAT units spaced by molten chains are interconnected by TPD bridges. Upon annealing, a crystalline phase, stemming from the parent hexagonal mesophase, is obtained with the molecular stacking direction lying in-plane. Transport measurements in the crystalline phase reveal an unusually high out-of-plane hole mobility of 0.17 cm 2 V −1 s −1 and a lower limit for the in-plane mobility of 0.05 cm 2 V −1 s −1 . The results suggest that the TPD segments bridging neighboring stacks of TAT columns are responsible for efficient hole transport in 3D.